2019
DOI: 10.7150/thno.31097
|View full text |Cite
|
Sign up to set email alerts
|

HCP5 is a SMAD3-responsive long non-coding RNA that promotes lung adenocarcinoma metastasis via miR-203/SNAI axis

Abstract: Introduction : Transforming growth factor-beta (TGFβ) signaling plays a vital role in lung adenocarcinoma (LUAD) progression. However, the involvement of TGFβ-regulated long non-coding RNAs (lncRNAs) in metastasis of LUAD remains poorly understood. Methods : We performed bioinformatic analyses to identify putative lncRNAs regulated by TGF-β/SMAD3 and validated the results by quantitative PCR in LUAD cells. We performed luciferase reporter and chromatin immunoprecipitation ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(93 citation statements)
references
References 49 publications
(49 reference statements)
3
90
0
Order By: Relevance
“…Furthermore, miR-203 has been proven to be involved in the expression of several cancerrelated factors. MiR-203 suppressed ovarian carcinoma progression by inhibiting Survivin expression [25] and inhibited epithelial-mesenchymal transition by decreasing Snail and Slug expression, which are regarded as biomarkers of the epithelial-mesenchymal transition process [27]. This evidence suggests that miR-203 could potentially become a cancer therapeutic target and prognostic biomarker.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, miR-203 has been proven to be involved in the expression of several cancerrelated factors. MiR-203 suppressed ovarian carcinoma progression by inhibiting Survivin expression [25] and inhibited epithelial-mesenchymal transition by decreasing Snail and Slug expression, which are regarded as biomarkers of the epithelial-mesenchymal transition process [27]. This evidence suggests that miR-203 could potentially become a cancer therapeutic target and prognostic biomarker.…”
Section: Discussionmentioning
confidence: 92%
“…[11][12][13] Some lncRNAs, such as HCP5, CAR10, NEAT1 and MALAT1, promote lung cancer metastasis via various mechanisms. 7,14,15 These findings suggest that the tumor metastasis-associated lncRNAs in lung cancer have potential prognostic implications. In the present study, we hypothesized that there were metastasis-associated lncRNAs in LUAD which were differentially expressed between metastatic and nonmetastatic primary cancer tissues, and the dysregulated lncRNA expression regulated the aggressiveness, or in general, the prognosis.…”
Section: Introductionmentioning
confidence: 83%
“…Several recent studies have focused on the involvement of lncRNAs in tumor metastasis because these lncRNAs have shown great promise in the discovery of new biomarkers for predicting prognosis in individual patients . Some lncRNAs, such as HCP5, CAR10, NEAT1 and MALAT1, promote lung cancer metastasis via various mechanisms . These findings suggest that the tumor metastasis‐associated lncRNAs in lung cancer have potential prognostic implications.…”
Section: Introductionmentioning
confidence: 99%
“…MiR‐203 expression was down‐regulated in NSCLC and negatively correlated with clinical tumour‐node‐metastasis (TNM) stages . Jiang et al demonstrated that HCP5 repressed miR‐203 acting as a molecular sponge, stabilized Snail and Slug, and in turn, promoted the invasion of lung cancer cells . Taken together, HCP5 up‐regulated the expression of Snail and Slug by sponging miR‐203 and activated the TGF‐β/SMAD signal pathway promoting metastasis of NSCLC.…”
Section: Main Molecular Mechanism Of Lncrna To Regulate the Metastasimentioning
confidence: 99%